Nitric oxide releasing lipid bilayer tethered on titanium and its effects on vascular cells - Elnaggar, Mahmoud A.; Han, Dong Keun; Joung, Yoon Ki (한국공업화학회, 2019)
The aim of this study was to investigate the feasibility and potential use of tethered lipid bilayer (tLB) membranes with a lipophilic nitric oxide (NO) donor (10-nitrooleate) incorporated into the bilayer to achieve the controlled release of NO from tLB membrane-anchored on a metal surface. NO releasing tLB membranes were prepared via two steps: (1) tethering phospholipids on a metal surface and (2) fusing NO donor containing liposomes with the lipids pre-tethered on the surface. Surface analyses using Fourier transform infrared (FTIR), fluorescent and confocal and atomic force microscopy (AFM) were utilized to prove the successful tLB formation on titanium surface. Bovine serum albumin and fibrinogen tests showed minimum adsorption on the tLB samples when compared with bare titanium plates. After the incorporation of 10-nitrooleate into the bilayer, the samples exhibited sustained NO release profiles up to 24 h. In vitro cell study demonstrated that NO releasing tLB has pleiotropic effects on endothelial cells and smooth muscle cells. Finally, these results open up a door for the potential use of bioactive gas releasing tLB for biomedical devices. (C) 2019 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.